2019
DOI: 10.33073/pjm-2019-019
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Petrol Metabolizing Bacteria Isolated from Contaminated Soil Samples Collected from Various Fuel Stations

Abstract: The present study aimed to isolate the high-efficiency petrol metabolizing thermophilic bacteria from petrol contaminated soil samples. Isolation was carried out through enrichment culture, serial dilution and pour plate methods using the petrol supplemented minimal salt media. The isolated bacteria were analyzed to document growth behavior, petrol removal efficiencies, antibiotic resistance profile, and biochemical characteristics. The 16S rRNA based phylogenetic analysis helped to reveal the identity of isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…CT10) and 48 hr ( Pseudomonas and Bacillus sp.) ( Liang et al 2018 ; Tian et al 2018 ; Muccee and Ejaz 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CT10) and 48 hr ( Pseudomonas and Bacillus sp.) ( Liang et al 2018 ; Tian et al 2018 ; Muccee and Ejaz 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various petroleum degraders have been biochemically characterized in previous studies and found positive for the assays like catalase test, MacConkey agar test, lactose fermentation, mannitol test, urea hydrolysis test, starch hydrolysis test, citrate test, carbohydrate utilization test, esculinase test, phosphatase test, PYR, ADH, β-D-glucosaminidase test, mannitol, sorbitol and inulin fermentation tests ( Muccee and Ejaz 2019 ; Hossain et al 2022 ). So, the present study’s findings are consistent with earlier research, as B. cereus has also been found positive for ADH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conditions used for PCR amplification were; initial denaturation for 5 min. at 95°C, 38 cycles of initial denaturation for 40 s at 94°C, annealing for 60 s at 58°C, extension for 30 s at 72°C, and final extension for 10 min at 72°C [20]. Amplified PCR products of 1500 bp were subjected to agarose gel electrophoresis and purified using Monarch DNA Gel Extraction Kit (Cat # T1030S BioLabs) and sent for sequencing to Macrogen.…”
Section: Methodsmentioning
confidence: 99%
“…Extracellular and intracellular metabolites were extracted using a previously reported protocol [20]. Supernatant of a bacterial culture was used as a source of extracellular metabolites and mixed with absolute methanol in equimolar concentration.…”
Section: Methodsmentioning
confidence: 99%